Process and outcome of outpatient psychotherapies under clinically representative conditions in Austria: protocol and feasibility of an ongoing study - Schaffler, Yvonne; Jesser, Andrea; Humer, Elke; Haider, Katja; Pieh, Christoph; Probst, Thomas; Schigl, Brigitte (Frontiers in Psychiatry, 2024)
Background: While most studies assessing psychotherapy efficacy are randomized-controlled trials conducted in research institutions or short clinical treatments, the understanding of psychotherapy effectiveness under regular, clinically representative conditions, particularly in outpatient practice, remains limited. Representative data examining the effectiveness of psychotherapy under real-world conditions in Austria is lacking.Aims and Methods: This paper introduces a naturalistic observational combined process-and outcome study, implementing a dual-perspective approach through standardised pre-and post-treatment questionnaires and evaluating changes in the therapeutic alliance after each session. Further, semistructured qualitative interviews aim to illuminate the personal experiences of patients and therapists. The primary objective of the presented study is to discern whether symptoms markedly decrease following therapy. A significant secondary goal is to trace the therapeutic alliance's evolution from both patient and therapist viewpoints, emphasising the alliance-outcome association and gender dynamics within the pairs. This paper discusses the project's feasibility after three years and shares key insights. Discussion: Recruitment for this study has posed substantial challenges due to psychotherapists' concerns regarding data protection, extensive documentation, and philosophical reservations about the study design. Consequently, we recruited fewer participants than initially planned. Despite these hurdles, qualitative data collection has shown notable success. Given psychotherapists' busy schedules and reluctance to participate, more potent external incentives or a legal obligation may be necessary to encourage participation in future studies.